Personal style blogs : appearances that fascinate - Findlay, Rosie (Intellect, 2017)
"The book charts the development of the style blogosphere and its transformation from an alternative, experimental space to one dominated by the fashion industry. Complete with examples of several famous fashion bloggers, such as Susie Lau, Rumi Neely, and Tavi Gevinson, the author explores notions of individuality, aesthetics, and performance on both sides of the digital platform. Findlay asks: what can style blogging teach us about women's writing and the performance of a private self online? And what drives style bloggers to carve a space for themselves online?"--Publisher's description